Nutritional factors associated with distribution of Mopani Worms in Mopani woodlands in Tsholotsho and Gwanda Districts, Zimbabwe: A comparative survey - Nunu, Wilfred Njabulo; Ncube, Buhlebenkosi; Dube, Oliver; Mpofu, Clever; Ndlovu, Brighton; Dzinomwa, Tariro; Khumalo, Nkosana (Nature Research, 2021)
Mopani worms are abundant in Gwanda and sporadic in Tsholotsho though the two areas have similar climatic conditions. The study sought to determine nutritional factors that could be associated with distribution of Mopani worms in these two districts. Ten sampling points in undisturbed Mopani woodlands were established in each district. Samples were collected and analysed in the lab to determine the levels of crude protein, tannin and natural detergent fbres levels in leaves and pH, Nitrates, Phosphates and Potassium levels in soil and Welch’s test, Wilcoxon-Mann-Whitney, Analysis of Variance and the Bonferroni Confdence Intervals were employed to test for signifcance in the observed diferences. Findings showed diferences in tree size and leaf length whilst the diferences of all other variables (non-extractible tannis, extractible tannis crude protein levels and natural detergent fbres) relating to leaf sample analysis were not statistically signifcant. Findings on soil sample analysis pointed out that Gwanda had higher pH, Phosphorus and Potassium levels whilst Nitrates were signifcantly higher in Tsholotsho. Diferences in the tree sizes and leaf sizes of the samples from the two sites show that there could be host selection based on these variables.